2018
DOI: 10.1116/1.5020128
|View full text |Cite
|
Sign up to set email alerts
|

Smallest microhouse in the world, assembled on the facet of an optical fiber by origami and welded in the μRobotex nanofactory

Abstract: In this study, the authors have demonstrated that it is possible to realize several three-dimensional (3D) micro-and nanostructures, by the fabrication of the smallest microhouse using a dual beam scanning electron microscope (SEM)/focused ion beam (FIB) Auriga 60 from Zeiss together with a six degree of freedom robot built with SmarAct components. In this new type of nanolab, cutting, etching, folding, assembling, and then welding thin membranes of silica on top of a cleaved optical fiber SMF28, or production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…According to Wu et al ( 2006 ), Polypyrrole-based micro-actuators can generate forces superior to 1 mN, which is more than enough force to manipulate micro/nano-objects inside a SEM. The 3 mm long cantilever, with a width of 400 μ m and a thickness of 106 μ m was inserted into a SEM (The used microscope is an Auriga 60 microscope produced by Zeiss with a big vacuum chamber that has a volume of 60 × 60 × 60 cm 3 , more details are available in Rauch et al, 2018 ), tested, characterized, and controlled using visual servoing. The cantilever was first mounted on a small 3D printed support, which contains copper tape to provide electrical connections, as shown in Figure 5a .…”
Section: Resultsmentioning
confidence: 99%
“…According to Wu et al ( 2006 ), Polypyrrole-based micro-actuators can generate forces superior to 1 mN, which is more than enough force to manipulate micro/nano-objects inside a SEM. The 3 mm long cantilever, with a width of 400 μ m and a thickness of 106 μ m was inserted into a SEM (The used microscope is an Auriga 60 microscope produced by Zeiss with a big vacuum chamber that has a volume of 60 × 60 × 60 cm 3 , more details are available in Rauch et al, 2018 ), tested, characterized, and controlled using visual servoing. The cantilever was first mounted on a small 3D printed support, which contains copper tape to provide electrical connections, as shown in Figure 5a .…”
Section: Resultsmentioning
confidence: 99%
“…Robotic arms and micro/nanotechnologies were combined to provide unique capabilities for cutting, etching, folding, assembling, and welding thin membranes on fiber facets. The enormous potential of this completely new way to conceive LOF platforms with unparalleled spatial control was recently demonstrated by Rauch et al They demonstrated the surprising capability of their new “µ-Robotex nanofactory” approach by creating the “smallest microhouse” in the world; this microhouse was assembled on the facet of an optical fiber based on origami and welding, as shown in Figure 4 [ 35 ].…”
Section: Lab-on-fiber Concept: a Technological Roadmapmentioning
confidence: 99%
“… Microhouse assembled with origami and welded on top of the facet of an optical fiber. Reprinted with permission from [ 35 ]. Copyright 2019, American Vacuum Society.…”
Section: Figurementioning
confidence: 99%
“…The pictures of the film have been made on an ad-hoc scientific equipment of FEMTO-ST institute named µRobotex platform [8]. This innovative powerful micro and nanofactory, is based on an Auriga 60 microscope produced by Zeiss.…”
Section: Basic Principle Of the Sem Microrobotic Platformmentioning
confidence: 99%
“…The film has also provided new robotic capabilities by developing a complete software that enables to perform high precision positioning in a semi-automatic mode when the current SEM micromanipulators in the world is only teleoperated. This robotic control enables to perform various operations of robotic micro-assembly in various application frames [8].…”
Section: Technological and Artistic Outcomesmentioning
confidence: 99%